2009
DOI: 10.1002/hep.22911
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 impedes hepatitis C virus infection in vitro and modulates liver CD81 expression #

Abstract: Human PCSK9 is known to enhance the degradation of membrane-bound receptors such as the hepatocyte low-density lipoprotein receptor (LDLR), ApoER2, and very low-density lipoprotein receptor. Because the LDLR is suspected to be involved in hepatitis C virus (HCV) entry, we also tested whether PCSK9 can affect the levels of CD81, a major HCV receptor. Interestingly, stable expression of PCSK9 or a more active membrane-bound form of the protein (PCSK9-ACE2) resulted in a marked reduction in CD81 and LDLR expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 36 publications
5
101
0
1
Order By: Relevance
“…VLDLR and apo-ER2, but not angiotensin-converting enzyme 2 (26) nor the high density lipoprotein receptor SR-BI, hepatocyte growth factor receptor HGFR, or transferrin receptor TfR (27). It was also shown previously that overexpression of PCSK9 in a rat hepatic cell line reduces the levels of LDLR mostly in transfected cells (15).…”
Section: Secreted Pcsk9 From Wt Hepatocytes Does Not Affect Ldlr In Pmentioning
confidence: 86%
“…VLDLR and apo-ER2, but not angiotensin-converting enzyme 2 (26) nor the high density lipoprotein receptor SR-BI, hepatocyte growth factor receptor HGFR, or transferrin receptor TfR (27). It was also shown previously that overexpression of PCSK9 in a rat hepatic cell line reduces the levels of LDLR mostly in transfected cells (15).…”
Section: Secreted Pcsk9 From Wt Hepatocytes Does Not Affect Ldlr In Pmentioning
confidence: 86%
“…The data showed that PCSK9 targets 2 hepatic HCV receptors for degradation, namely the LDLR and the tetraspanin protein CD81. 71 Furthermore, it was recently reported that other viruses bind to cell surface LDLR family members to enter and infect cells, including vesicular stomatitis virus that likely uses the LDLR and LRP1 as entry receptors. 72 These results suggested that although inhibiting PCSK9 may be beneficial to reduce the levels of circulating LDL-C, it potentially could enhance the infectivity of certain viruses, such as HCV, vesicular stomatitis virus, the common cold rhino virus, and rous sarcoma virus.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 99%
“…Recently, it was shown that liver expression of CD81 is markedly increased in Pcsk9-knockout mice and that the HCV receptor CD81 protein is downregulated independently from the LDLR. 71 Therefore, it was proposed that the plasma level and activity of PCSK9 could modulate HCV infectivity in humans. In summary, the LDLR and CD81, 2 HCV entry receptors are dose dependently downregulated by PCSK9, resulting in the reduction of the cellular infectivity of HCV in mice.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Up to 30% of circulating PCSK9 is associated with LDL, regardless of LDLR expression, probably by increasing both the hepatic and intestinal synthesis of apoB, the LDL particle structural protein 21) . Previ- tect against HCV in mice by downregulating the hepatic expression of CD81 and HCV entry receptors, resulting in a decreased HCV cellular infection rate, although this has not been shown in humans 38) . Moreover, PCSK9 deficiency results in delayed hepatocyte proliferation and enhanced apoptosis following partial hepatectomy, which can be rescued by feeding the mice a high-ch olesterol diet 23) .…”
Section: Main Pathogenic Hypothesis Of Atherosclerosismentioning
confidence: 99%